TANGGUNG JAWAB SOSIAL PERUSAHAAN: ANTARA KEWAJIBAN DAN KESUKARELAAN - Nadapdap, Binoto; Hutabarat, Sylvana M D (Jurnal Yuridis, 2015)
Social Corporate Responsibility (CSR) is introduced in Article 74 of Act No. 40/2007 regarding Company Law. Formerly CSR is a voluntary but since Act 40/2007 come to enforce, social responsibility become mandatory for the company which has its activity in mining sector. Besides Act No. 40/2007, few regulations also contained principle of Social Corporate Responsibility. This paper will discuss the social responsibility that obligation for the company. How the CSR be seen through organization view and moralistic view. Beside that the company also has other responsibilities such as responsibilities both internally and externally. Other responsibilities associated with it is the economic responsibility and legalliability that has also become part of the company obligation.